Komunikasi Interpersonal Ustadz dengan Santri dalam Pembinaan Akhlak Pondok Pesantren Subulul Huda Kabupaten Madiun - Marik Atul Muzayyanah; Muhammad Syarifuddin; Latutik Mukhlisin; Malik Ibrahim (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2024)
Interpersonal communication is one of the methods that can be utilized by a Ustadz in educating his Santri so that their morals can be better, therefore moral development is an urgency in order to get quality and morally good people. One of the interactions between ustadz and santri takes place effectively through interpersonal communication, which involves face-to-face interaction between two or more individuals. The purpose of this study was to determine how interpersonal communication between Ustadz and Santri in fostering morals, supporting and inhibiting factors of interpersonal communication. This research uses a type of qualitative research with a descriptive approach. The techniques for data collection include observation, interviews, and documentation. Data analysis follows the steps of data reduction, data presentation, and drawing conclusions. The validity of the data is ensured through source triangulation.The result of this study is that Ustadz succeeded in implementing interpersonal communication in fostering santri morals with the theory of interpersonal communication from Josep A DeVito, namely the existence of openness, equality, empathy, support, and positiveness. Communication runs effectively because of the support between the two parties, but not all of them.